Computer architecture and parallel processing - Hwang, Kai.; Briggs, Faye A. ([S.l.] : Mcgraw-Hill College, 1984)
USED VERY GOOD CONDITION, HARD COVER, TIGHT BINDING, CLEAN PAGES, READY TO SHIP (BXX-553)